Marketing Management / Analysis, Planning, Implementation and Control - Kotler Philip (Prentice Hall, 1991)
Understanding Marketing Management, Analyzing Marketing Opportunities, Researching and Selecting Target Markets, Designing Marketing Strategies, Planning Marketing Programs, Organizing and Implementing and Controlling Marketing Effort, Indices.
Understanding Marketing Management, Analyzing Marketing Opportunities, Researching and Selecting Target Markets, Designing Marketing Strategies, Planning Marketing Programs, Organizing and Implementing and Controlling Marketing Effort, Indices.